informed Consent in minors for gender reassignment treatments in Colombia - Ortíz Díaz, Brenda Juliana; Palacio Medina, Angélica; Correa Martínez, César Alberto (Scientific journal of social studies, 2023)
This work is the result of qualitative research with an analytical-descriptive method that aims to focus on relevant aspects of informed consent in minor sex reassignment procedures in Colombia. In addition, it is proposed to describe and analyze the mentioned phenomenon in the national legal system.The analyzed problem is related to information on health, identity and free development of personality as fundamental rights recognized in the constitutional framework of medical care. Regarding the possibility of recognizing the children and teenagers decisions, it is based on the will autonomy that allows making relevant choices related to sexual freedom and protection of their rights. In consequence, we can conclude that the Colombian legal system allows the performance of surgeries and hormonal procedures for the reassignment of sex to minors, only when certain requirements are met in order to ensure their well-being.